2020
DOI: 10.1021/acs.langmuir.0c02794
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Cosolvent Effect on Lignin–Cellulose Adhesion

Abstract: Understanding and controlling the physical adsorption of lignin compounds on cellulose pulp is a key parameter for a successful optimization of organosolv processes. The effect of binary organic-aqueous solvents on the coordination of lignin to cellulose was studied with molecular dynamics simulations, considering ethanol and acetonitrile as organic co-solvents in aqueous solutions in comparison to their mono-component counterparts. The structures of the solvation shells around cellulose and lignin, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Indeed, our previous analysis of the MD trajectories revealed well-organized and structured first solvation shells around O–Cα and O–Cγ sites in all the solvents. 65 The previously studied radial distribution functions of N(ACN)–O–CMe in the G- b -G dimer revealed acetonitrile coordination to the oxygen atoms that are bound to methyl carbons. 42,65 The chemical shift of the methyl carbon appears, however, to be only a little affected (by a maximum of 3 ppm) by the presence of EtOH co-solvent, and almost not affected by ACN co-solvent.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, our previous analysis of the MD trajectories revealed well-organized and structured first solvation shells around O–Cα and O–Cγ sites in all the solvents. 65 The previously studied radial distribution functions of N(ACN)–O–CMe in the G- b -G dimer revealed acetonitrile coordination to the oxygen atoms that are bound to methyl carbons. 42,65 The chemical shift of the methyl carbon appears, however, to be only a little affected (by a maximum of 3 ppm) by the presence of EtOH co-solvent, and almost not affected by ACN co-solvent.…”
Section: Resultsmentioning
confidence: 94%
“…Dynamic (time-averaged) 13 C chemical shift and conformational effects Our previous studies 37,65 on the evolution of lignin dimer conformations along the equilibrium dynamics in several solvents revealed that the b-O-4 linked guaiacyl dimer has the smallest solvent accessible surface area and the most stacked conformation in water. This effect has been attributed to lignin-water hydrophobic interactions favouring the phenolic G ring-ring interactions, instead of lignin-water interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith and co-workers showed that the ethanol/water binary mixture tends to phase separation on the cellulose surface, which can enhance the deconstruction of the cellulose crystal. Aguilera and co-workers showed that, in ethanol/water binary mixtures, the competition between ethanol and water for the same oxygen sites on cellulose leads to more effective disruption of the cellulose–lignin complex at increasing ethanol concentrations. From these studies, we believe if we introduce cellulose into our methanol/water system, methanol and water would show similar behaviors for the dissolution of cellulose and disrupt the adsorption of lignin on cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that water dissolved hemicellulose, G-unit, and those with β-O4 linkage of lignin, whereas ethanol extracts G and S units along with β-5 and β-β linkages. Computational work by Aguilera and co-workers 13 suggested that ethanol/ water and acetonitrile/water lead to effective disruption of lignin−cellulose binding. This study showed that lignin precipitation on cellulose was disrupted upon adding 50 and 75 wt % ethanol into the pure water, due to the cosolventinduced conformational transition and the expulsion of water from cellulose solvation shells.…”
Section: ■ Introductionmentioning
confidence: 99%